Accelerating progress in improving diets and nutrition in Ethiopia - Baye, Kaleab; Hirvonen, Kalle (International Food Policy Research Institute, 2020)
Ethiopia has witnessed significant reductions in child mortality, undernutrition, and communicable diseases, but more substantial and faster progress is still needed. The rise in obesity and in noncommunicable diseases, particularly in urban areas, is alarming and requires urgent policy and programmatic attention. Unhealthy diets drive both undernutrition and obesity and are the underlying cause of significant proportion of both communicable and non-communicable diseases. Maintaining the relatively high breastfeeding practices and increasing the diversity of diets will be critical to improving nutrition in Ethiopia. Implementation of effective nutrition messaging that shapes consumer behavior to adopt healthy dietary patterns, while bridging gaps in both the reach and the quality of such messaging is warranted. The health extension program, which is the cornerstone of the transformation of the health sector, may need to be redesigned in a way that improves its reach and the quality of the services it provides and minimizes the risk of burnout of frontline health workers. Interventions focusing on making healthy diets available, affordable, and accessible are urgently needed.